KDIGO Guidelines and Kidney Transplantation: Is the Cystatin‐C Based Recommendation Relevant?. Issue 8 (24th March 2015) - Masson, I.; Maillard, N.; Cavalier, E.; Alamartine, E.; Mariat, C.; Delanaye, P.
<x xml:space="preserve">Abstract</x> The KDIGO guidelines propose a new approach to diagnose chronic kidney disease (CKD) based on estimated glomerular filtration rate (GFR). In patients with a GFR value comprised between 45 and 59 mL/min/1.73 m2 as estimated by the CKD‐EPI creatinine equation (eGFRcreat), it is suggested to confirm the diagnosis with a second estimation using the CKD‐EPI cystatin C‐based equations (eGFRcys/eGFRcreat‐cys). We sought to determine whether this new diagnostic strategy might extend to kidney transplant recipients (KTR) and help to identify those with decreased GFR. In 670 KTR for whom a measured GFR was available, we simulated the detection of CKD using the two‐steps approach recommended by the guidelines in comparison to the conventional approach relying on creatinine equation. One hundred forty‐five patients with no albuminuria had eGFRcreat between 45 and 59 mL/min/1.73 m2. Among them, 23% had inulin clearance over 60 mL/min/1.73 m2 and were thus incorrectly classified as CKD patients. When applying the Kidney Disease: Improving Global Outcomes (KDIGO) strategy, 138 patients were confirmed as having a GFR below 60 mL/min with eGFRcreat‐cys. However, 21% of them were misclassified in reference to measured GFR. Our data do no not support the use of cystatin C as a confirmatory test of stage 3 A CKD in KTR.